AN INTUITIONISTIC FUZZY APPROACH FOR COVID-19 SURVEY ANALYTICS (Revista Inclusiones, 2021)
In 2020 there were numerous studies on the impact of COVID-19 on the human body. In this paperwe target to analyze the results from a sociologic survey over a very big group of responders whoseanswers comprise a big data set. We suggest an approach for analysis based on a simple acquisitionof intuitionistic fuzzy sets where intuitionistic fuzzy degrees are assigned on the dimensions health,socio-economic status, social and family relations in the context of COVID-19 for the purposes of dataanalysis and visualization. The intuitionistic fuzzy sets of assessments are based on the classicalAtanasov’s intuitionistic fuzzy set theory and the subsequent analyses use an approach forcomparison between such sets based on Intuitionistic Fuzzy norms and distances. We apply thesuggested approach on a real big dataset, obtained from the Survey of Health, Ageing and Retirementin Europe (SHARE) Wave 8. COVID-19 Survey 1. Release version: 0.0.1. beta. SHARE-ERIC. Dataset. DOI: 10.6103/SHARE.w8cabeta.001 (Börsch-Supan, A. 2020). As a result, EU countries areclassified into several groups that segment the database in terms of health, socio-economic status,social and family relationships in the context of COVID-19. The methodology we offer is broad enoughto be extended to other research or disciplines.